Cathepsin V regulates cell cycle progression and histone stability in the nucleus of breast cancer cells - Sereesongsaeng, Naphannop; Burrows, James F.; Scott, Christopher J.; Brix, Klaudia; Burden, Roberta E. (Frontiers in Pharmacology, 2023)
We previously identified that Cathepsin V (CTSV) expression is associated with poor prognosis in ER+ breast cancer, particularly within the Luminal A subtype. Examination of the molecular role of the protease within Luminal A tumours, revealed that CTSV promotes tumour cell invasion and proliferation, in addition to degradation of the luminal transcription factor, GATA3, via the proteasome. In this work we have identified that CTSV has an impact on breast cancer cell proliferation, with CTSV depleted cells exhibiting delayed progression through the G2/M phase of the cell cycle. Further investigation has revealed that CTSV can control nuclear expression levels of histones H3 and H4 via regulating protein expression of their chaperone sNASP. We have discovered that CTSV is localised to the nuclear compartment in breast tumour cells, mediated by a bipartite nuclear localisation signal (NLS) within the CTSV sequence and that nuclear CTSV is required for cell cycle progression and histone stability in breast tumour cells. Collectively these findings support the hypothesis that targeting CTSV may have utility as a novel therapeutic target in ER+ breast cancer by impairing cell cycle progression via manipulating histone stabilisation.